The ten faces of innovation : IDEO's strategies for beating the devil's advocate and driving creativity throughout your organization. - Kelley, Tom, 1955-; Littman, Jonathan, 1958- (New York : Doubleday, 2005)
The role of the devil's advocate is nearly universal in business today. It allows individuals to step outside themselves and raise questions and concerns that effectively kill new projects and ideas, while claiming no personal responsibility. Nothing is more potent in stifling innovation as Tom Kelley points out in The Ten Faces of Innovation. Over the years, Tom has observed a number of roles that people can play in an organization to foster innovation and new ideas while offering an effective counter to naysayers. Among these approaches are the Anthropologist, the person who goes into the field to see how customers use and respond to products, to come up with new innovations; the Cross-Pollinator, who mixes and matches ideas, widely disparate people, and technologies to create new ideas that can drive growth; and the Hurdler, who instantly looks for ways to overcome the limits and challenges to any situation. Filled with engaging stories of how companies such as Kraft, Samsung, and Procter & Gamble have incorporated IDEO's thinking to transform the customer experience, The Ten Faces of Innovation is an extraordinary guide to nurturing and sustaining a culture of continuous innovation and renewal.
Keywords: Ontwerpmethodologie; Technische innovatie